The Amanah Rakyat Negeri Sabah Enactment 1990 - George, Mary (Journal of Malaysian and Comparative Law, 2019)
This note is a quest to determine first, the nature and status of the trust created by the Amanah Rakyat Negeri Sabah Enactment 1990, which may be called the "trust instrument" of the Sabah Legislative Assemly and second to emphasize the importance of construing the Amanah Rakyat Negeri Sabah Enactment 1990 as a charitable trust such that the passing of the above-mentioned Enactment by the Government of Sabah is intra-vires the Federal Constitution. The former is done by comparing and contra-distinguishing the Enactment with principally the Trustee Act 1949 and decided cases, whilst the later is done by reference to the Federal Constitution and other legislation in force in Malaysia, namely: The Trusts (State Legislative Competency) Act 1949, Incorporation (State Legislature Competency) Act 1962, National Trust Fund Act 1952, Trustees (Incorporation) Sabah Cap. 148 and Amendment Ordinance 8/1955, Trust Companies Act 1949 in relation to section 3(1)(b) of the Civil Law Act 1956.